Brittle-viscous deformation cycles in the dry lower continental crust - Menegon, Luca; PENNACCHIONI, GIORGIO (Copernicus Publications, 2015)
Many rheological models of the lithosphere (based on “strength envelopes”) predict a weak aseismic lower crust below the strong brittle upper crust. An alternative view, based on the distribution of crustal seismicity, is that the lower crust could also be strong and seismic. It has been suggested that a strong, seismogenic lower crust results from the dry conditions of granulite facies rocks, which inhibit crystal plastic flow. This study investigates exhumed networks of shear zones from Nusfjord (Lofoten, northern Norway) to understand initiation and localization of viscous shearing in the dry lower crust. In the study area, different sets of ultramylonitic shear zones are hosted in the massive coarse-grained anorthosite. Metamorphic conditions of 720 ◦C, 0.9 GPa have been estimated for ductile deformation using amphibole- plagioclase geothermobarometry. Field evidence indicates that ductile shearing exploited pseudotachylyte veins and the associated damage zone of extensive fracturing. Undeformed pseudotachylyte veins locally overprint mylonitic pseudotachylytes suggesting that frictional melting occurred at the same metamorphic conditions of mylonitization. The deep crustal origin of the pseudotachylytes is also indicated by (1) the presence of microlites of labradoritic plagioclase and clinopyroxene, and of dendritic garnet, and (2) the recrystallization of clinopyrox- ene in the damage zone flanking the pseudotachylyte veins. Therefore the association of pseudotachylytes and mylonites records brittle-viscous deformation cycles under lower crustal conditions. The ultramylonites show phase mixing, fine grain size (5-20 μm) and equant shape of all minerals. Nucleation of amphibole in triple junctions and dilatant sites is common. EBSD analysis indicates that the minerals in the matrix are internally strain free and do not show a crystallographic preferred orientation. Taken together, these observations suggest that diffusion creep and grain boundary sliding were the main deformation mechanisms in the ...